2022
DOI: 10.1111/ene.15310
|View full text |Cite
|
Sign up to set email alerts
|

RFC1 repeat expansions: A recurrent cause of sensory and autonomic neuropathy with cough and ataxia

Abstract: Background and purpose Ataxia and cough are rare features in hereditary sensory and autonomic neuropathies (HSAN), a group of diseases of mostly unknown genetic cause. Biallelic repeat expansions in RFC1 are associated with cerebellar ataxia, neuropathy, and vestibular areflexia syndrome (CANVAS). This study aimed to investigate the prevalence of RFC1 repeat expansions in a cohort of HSAN patients. Methods After unremarkable whole‐exome sequencing (WES) analysis, we performed repeat‐primed PCR to detect intron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Several patients had chronic cough (3/7, 42.9%), autonomic neuropathy (5/15, 33.3%), muscle cramps (4/9, 44.4%), and hyperCKemia (7/13, 53.8%). RFC1 -related neuropathy is often accompanied by chronic cough and autonomic disturbance [ 6 , 35 ], which are suggestive signs of RFC1 -related disorders among IPNs. To date, hyperCKemia and muscle cramps have been reported only in patients carrying (ACAGG)exp [ 13 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several patients had chronic cough (3/7, 42.9%), autonomic neuropathy (5/15, 33.3%), muscle cramps (4/9, 44.4%), and hyperCKemia (7/13, 53.8%). RFC1 -related neuropathy is often accompanied by chronic cough and autonomic disturbance [ 6 , 35 ], which are suggestive signs of RFC1 -related disorders among IPNs. To date, hyperCKemia and muscle cramps have been reported only in patients carrying (ACAGG)exp [ 13 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of clinical symptoms at disease onset revealed that the initially reported symptoms of patients with SFN do not differ between idiopathic SFN and SFN associated with Sjögren’s syndrome. This symptom overlap might also be amplified through autonomic involvement of SFN which can lead to dry eyes and mouth symptoms [ 30 , 31 ]. Also, neither assessment of CSF parameters such as cell count, total protein, Q-albumin, lactate, nor evaluation for oligoclonal bands was helpful in distinguishing the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed a high number of individuals with RFC1 repeat expansion in a preselected cohort of patients with sensory CIAP (53%), but also some patients with minor and pronounced motor involvement 125 . RFC1 repeat expansions have also been described in patients with HSAN, cough and ataxia 127 . RFC1 encodes the large subunit of replication factor C, which is required for eukaryotic DNA replication and repair.…”
Section: [H2] Neurotrophin Signallingmentioning
confidence: 97%